2018
DOI: 10.3389/fped.2018.00266
|View full text |Cite
|
Sign up to set email alerts
|

Translating Sepsis-3 Criteria in Children: Prognostic Accuracy of Age-Adjusted Quick SOFA Score in Children Visiting the Emergency Department With Suspected Bacterial Infection

Abstract: Background: Recent attempts to translate Sepsis-3 criteria to children have been restricted to PICU patients and did not target children in emergency departments (ED). We assessed the prognostic accuracy of the age-adjusted quick Sequential Organ Failure Assessment score (qSOFA) and compared the performance to SIRS and the quick Pediatric Logistic Organ Dysfunction-2 score (qPELOD-2). We studied whether the addition of lactate (qSOFA-L) would increase prognostic accuracy.Methods: Non-academic, single-center, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 31 publications
2
56
2
3
Order By: Relevance
“…Overall, the LqSOFA demonstrates superior discriminative ability than that reported with the qSOFA in the pediatric population, both in the current study and compared with previous research. 6,9,30 In the current study, the LqSOFA revealed the greatest positive predictive value of all 4 scoring systems, although this was only 34%. The low values for positive predictive value seen across all scoring systems likely reflect the low prevalence of sepsis within the ED population and highlight the difficulty in identifying such cases.…”
Section: Figurecontrasting
confidence: 56%
See 4 more Smart Citations
“…Overall, the LqSOFA demonstrates superior discriminative ability than that reported with the qSOFA in the pediatric population, both in the current study and compared with previous research. 6,9,30 In the current study, the LqSOFA revealed the greatest positive predictive value of all 4 scoring systems, although this was only 34%. The low values for positive predictive value seen across all scoring systems likely reflect the low prevalence of sepsis within the ED population and highlight the difficulty in identifying such cases.…”
Section: Figurecontrasting
confidence: 56%
“…With a cutoff of $2, the score revealed excellent specificity but was limited by a relatively low sensitivity, consistent with sensitivities reported for the qSOFA in both adults and children. [7][8][9][10] Given that the these scores are designed as tools to aid clinician decision-making, rather than simply predict outcome, it has been argued that this rate of falsenegatives is unacceptably high. 10 However, a cutoff of $1 for the…”
Section: Lqsofamentioning
confidence: 99%
See 3 more Smart Citations